The factors affecting persistent pneumothorax and mortality in neonatal pneumothorax - Esme, Hıdır; Doğru, Ömer; Eren, Şevval; Korkmaz, Mevlüt; Solak, Okan (The Turkish Journal of Pediatrics, 2008)
The aim of this study was to present our experience in management of neonatal pneumothorax and factors contributing to persistent pneumothorax and mortality. Forty-two newborns were analyzed according to gestational age, birth weight, Apgar score, age of admittance, type of delivery, mother’s age, side of pneumothorax, causes of pneumothorax, accompanying disorders, tube thoracostomy and mechanical ventilation durations, mean hospital stay, and deaths. Sixteen patients (38%) weighed less than 2500 g and 28 (66%) were preterm. The mean Apgar score at 5th minute was 6.2 (2-10). The pneumothorax was bilateral in 9 patients (21%). There was a defined underlying lung pathology in 26 (61%) patients and accompanying disorder in 14 (33%). Mean tube thoracostomy duration was 5 days (2-12). Twenty-five patients (59%) needed mechanical ventilation. Overall 10 babies died. Our findings indicated that underlying primary lung pathology, need for mechanical ventilation, and bilateral pneumothorax were major determinants of persistent pneumothorax and mortality in newborns.